Mother’s Behaviour in Using Smartphone to Find Child’s Health Information in Pontianak City - Fithriyyah Fithriyyah; Rini Andriani; Mitra Handini (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Background. Smartphone is the main communication device that provides various information including child health information nowadays. Objective. To find out the overview of smartphone usage among the mothers to seek out child’s health information. Methods. An observasional descriptive study with cross sectional approach in 232 subjects. The data was obtained from 4 primary health care: Alianyang, Kampung Bali, Pal 3, and Karya Mulia. Result. There are 61.7% of mothers use smartphone as the main media to find obtain child health information. Most of the subject, 44.4% mothers are moderate duration users, 53.9% of mothers low frequency users, and 27.7% of mothers use smartphone for communication (call message). There are 34.7% of mothers choose social media as a reading source, 75.9% of mothers have browsing duration for 15-30 minutes, and mothers practicing the information they get from smartphone (54.7%). Conclusion.  Smartphones is the main information media for mothers, the average duration of use is 1-3.5 hours/day, the frequency of checking is less than 10 times/day, with the main function as communication device. Mothers use social media as the main source for child’s health information through smartphone, with browsing duration of 15-30 minutes and they practice the information obtained from smartphone.